Implementation Of Continuity Of Care (CoC) In Midwifery Care - Ainun Jariyah; Raehan Raehan; Eka Mustika Sari Abukasim; Rezqiqah Aulia Rahmat; Sulistyani Prabu Aji (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Continuity of The Continuity of Care (CoC) is a continuous approach to midwifery care, encompassing pregnancy, childbirth, postpartum, newborn care, and family planning services. This approach positions midwives as the primary providers of continuous care, thus improving service quality, maternal satisfaction, and reducing the risk of maternal and neonatal complications. This study aims to determine the application of Continuity of Care (CoC). of Care in midwifery care. The study used a descriptive analytical design with a cross-sectional approach. The study sample consisted of 40 mothers who received continuous midwifery care, selected using a purposive sampling technique. Data were collected through observation sheets and questionnaires. The results showed that most mothers received midwifery care with good implementation of CoC, especially in the aspects of pregnancy and childbirth. It was concluded that the implementation of CoC in midwifery care plays an important role in improving the quality of midwifery services and the experience of mothers during the reproductive period.